The Role of Regional Supervisory Assembly on Notary Duty - Muhammad Jaduk Chusana; Gunarto Gunarto; Setyawati Setyawati (Sultan Agung Notary Law Review, 2021)
Supervision of the Notary Profession is the authority of the Minister of Law and Human Rights. In carrying out supervision, the Minister establishes a Notary Supervisory Council which is tiered. The smallest Supervisory Council that carries out the supervisory and inspection functions is the Regional Supervisory Council (MPD). The problem is that MPD has limitations in exercising its supervisory authority and examining notaries in Sleman Regency. This research uses an empirical juridical approach, the research specifications are library research and field research. Source of data used in the form of primary data obtained by interview. Secondary Data with Literature Study. Qualitative Analysis. The problem is analyzed using the theory of authority and the theory of legal certainty. Based on the research results, it can be concluded that 1) Efforts to develop and supervise Notaries, MPD Sleman Regency are preventive activities, and include coaching activities for Notaries in their jurisdiction. 2) The implementation of supervision that must be carried out by MPD Sleman Regency has not been maximally carried out, this can be seen from: a) Supervision activities are mostly carried out around receiving reports from each Notary in Sleman Regency regarding Notary Protocol; b) MPD Sleman Regency inspection to check each Notary in their respective offices to see the office situation, this has not been maximally done because of the Covid 19 pandemic which requires examinations to be carried out online. 3) MPD Sleman Regency finds it difficult to know about violations of office.